RETRACTED: Seizure freedom without seizure medication following stereoelectroencephalography implantation: a case report of drug-resistant post-traumatic epilepsy - Tran, Alexander; Bunch, Marjorie (Frontiers in Neurology, 2024)
Achieving seizure freedom following failure of several antiseizure medications (ASMs) is rare, with the likelihood of achieving further control decreasing with each successive ASM trial. When cases of drug-resistant epilepsy arise, a diagnostic procedure known as stereoelectroencephalography (sEEG) can be used to identify epileptogenic zones (EZ) within the brain. After localization of these zones, they can be targeted for future surgical intervention.Here, we describe a case of complete seizure freedom off medication after sEEG without resection or other therapeutic intervention. In 2017, a 36-year-old right-handed male presented with drug-resistant epilepsy stemming from prior traumatic brain injury. Due to ongoing seizures, in 2020 a robotic-assisted sEEG electrode placement procedure was employed to localize the seizure onset zone. During sEEG monitoring, a single event was captured where the patient had dysarthric speech, left arm dystonic flexion, and difficulty responding to questioning. Notably, this event had no sEEG correlate, suggesting seizure occurrence in a region not monitored by implanted electrodes, which prompted the placement of scalp electrodes following this event. However, no further clinical events consistent with seizure were provoked through the remainder of recording. Following the 13-day admission, the patient chose to self-discontinue all seizure medications and has remained seizure free as of October 2023, more than 3.5 years later. While sEEG is considered a relatively safe procedure for seizure localization in drug resistant epilepsy, the possibility of microlesions created by sEEG depth electrodes remains largely unexplored. Further evaluation should be performed into potential tissue injury produced by depth electrode insertion.